Curse of the were-wiener - Vernon, Ursula (New York : Dial Books for Young Readers, 2010)
When Danny Dragonbreath's best friend Wendell the iguana is bitten by one of the hot dogs from his school lunch, he begins to turn into a were-wiener.
Keywords: Dragons -- Juvenile fiction; Iguanas -- Juvenile fiction; Frankfurters -- Juvenile fiction; School lunchrooms, cafeterias, etc. -- Juvenile fiction; Schools -- Juvenile fiction; Dragons -- Fiction; Iguanas -- Fiction; Frankfurters -- Fiction; School lunchrooms, cafeterias, etc. -- Fiction; Schools -- Fiction; Humorous stories